Dear society, respectable educational community of Kharkiv region! - Astakhova , K. (New Collegium, 2021)
You are sincerely greeted by a young and ambitious educational institution - Kharkiv Humanities University "People’s Ukrainian Academy", which is celebrating its first 30th anniversary.